Culture in «restriction». The cultural experience of the imaginary and the real space - Micheli, Anna (The Greek Review of Social Research, 2020)
We are in the process of a global dramatic health crisis, affecting our lives, our livelihoods, the social and cultural tissue of society. Covid - 19 has created a state of emergency which, among other things, brings the entire cultural sector (mobile, immovable and intangible cultural heritage) into an unexpected state, imposing the suspension of almost all its processes and worldwide operating networks or in intra-social scale setting, at the same time, an ever-present, substantial reflection, regarding the degree of sustainability of modern cultural strategies and the relevance between its diffusion practices, human behavior and response in times of extreme (global) events.. Contributing to a broader interdisciplinary discussion, the purpose of this text is to describe the context of cultural reality (real space and imaginary) as it is experienced through the generality of the crisis experience in the field of cultural life.